Total Hip Arthroplasty for Avascular Necrosis in a Patient With Hemophilia B - Siddhartha Dandamudi, BBA; Joyee Tseng, BS; John Ratz, BS; Lisa Boggio, MD, MS; Brett R. Levine, MD, MS (Arthroplasty Today)
Avascular necrosis (AVN) of the femoral head accounts for up to 10% of all total hip arthroplasties performed annually. Typically associated with intravascular coagulation, AVN is extremely rare in patients with bleeding disorders such as hemophilia B. In this report, we describe the therapeutic management of a 46-year-old male with hemophilia B, presenting with chronic left hip pain and AVN of the femoral head. He presented with progressive groin pain for 6 months and was unable to ambulate without the assistance of crutches. Radiographs showed evidence of degenerative joint disease secondary to AVN of the femoral head. After exhausting treatment options, the patient elected to proceed with an elective total hip arthroplasty. Intricate preoperative planning and hemophilia management were required by a multidisciplinary team to mitigate bleeding risks and promote success of the surgery. Postoperatively, the patient experienced a short-term rise in creatinine, but experienced no bleeding complications. The long-term follow-up revealed significant functional improvement without any complications of hemophilia B. There are no reports outlining AVN in hemophilia B (factor IX deficiency) or step-by-step treatment strategies for successful hip replacement in these patients.